The prevalence of non-sentinel lymph node metastasis among breast cancer patients with sentinel lymph node involvement and its impact on clinical decision-making: a single-centred retrospective study - Ding, Jingxian; Jiang, Xiaoliu; Huang, Zhaohui; Ji, Qiao; Long, Jie; Cao, Yali; Guo, Yonghong (Oncology Reviews, 2024)
Background Sentinel lymph node biopsy (SLNB) has become standard procedure for early breast cancer patients with clinically node negative disease. The patients with SLN metastasis normally underwent axillary lymph node dissection (ALND). However, the metastatic status of non-sentinel Lymph nodes (non-SLNs) varied significantly in different reports. Here, we evaluated the prevalence of non-SLNs metastasis among breast cancer patients with sentinel lymph node metastasis and its impact on clinical decision-making. Materials and Methods We identified 892 female patients with operable cT1-3N0 invasive breast cancer who underwent ALND in our center due to SLN metastasis from 2017 to 2023, retrospectively. The prevalence of non-SLN metastasis among different clinicopathological traits and its correlation with the number of positive SLNs were analyzed. The optimal clinical decision-making was generalized. Results The median number of SLN+, SLN, non-SLN+ and non-SLN was 2, 4, 1 and 14 among the enrolled 892 female patients, respectively. 504 (56.50%) patients with SLN + had at least one metastatic lymph node in the harvested non-SLNs. Among the enrolled 892 female patients, 435 (48.77%) patients with 1 positive SLN, of which 180 (41.38%) had at least one additional metastatic non-SLNs. 242 (27.13%) patients with 2 positive SLNs, of which 146 (60.33%) had at least one metastatic non-SLNs. For the rest 215 (24.10%) patients with at least 3 metastatic SLNs, 178 (82.79%) had at least one metastatic non-SLNs. In the univariate analysis, the non-SLNs metastatic status was correlated with the number of SLNs+, tumor size, tumor grade, lymphovascular invasion (LVI) and molecular subtypes, but not histopathologic type. In the multivariate analysis, the risk of additional non-SLNs metastasis correlated with the number of SLNs+, SLNs, non-SLNs and LVI. Conclusion Omiting ALND in patients with higher non-SLNs + rate outside the American College of Surgeons Oncology Group (ACSOG) Z0011 and the European Organization for Research and Treatment of Cancer (EORTC) 10,981–22023 AMAROS criteria should be considered with caution in clinical decision-making. To evaluate whether axillary radiotherapy and ALND provides equivalent regional control in breast cancer patients with obvious residual metastatic lymph nodes undesected in the axilla, a well-matched prospective randomized controlled trial is an urgent need.